Islamic Bank’s Performance In The Light of Competition and CSR - Tumewang, Yunice Karina; Maharani, Novita Kusuma (Universitas Muhammadiyah Yogyakarta, 2019)
This study aims to examine the effect of competition and Corporate Social Responsibility (CSR) disclosure toward Islamic banks? financial performance. It used Generalized Least Square with panel data of Islamic Banks in ASEAN and GCC from 2012-2016 obtained from Orbis Bank Focus. H-Statistic (Panzar-Rosse) test was employed to measure the degree of competition and the relationship between variables. This study found that competition contributes a negative effect toward performance of Islamic banks, while CSR contributes a positive effect toward performance of Islamic banks. The result of this study suggests the management of Islamic banks to be more aware of the importance of management of CSR programs for the acceleration of SDGs set by UN as well as survival of companies in the future. Additionally, this study would like to support to push ahead government plan to strengthen domestic Islamic bank through consolidation or a merger of state-owned Islamic banks in order to lower the degree of competition which ultimately leads to a better performance of Islamic banks as well as an enhanced financial deepening in Indonesia.